Activité antibactérienne des feuilles d’Argania spinosa de la région de Mostaganem - Abbes, Maghnia (My University, 2023)
Our work aims to know the evaluation of the antibacterial effects of extract of the leaves of the argan tree (Argania spinosa L. Skeels against six test pathogenic strains: S. aureus ATCC 33862, Klebsiella pneumoniae ATTC 13883, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Salmonella typhimurium ATCC 14028 and a mushroom: Candida albicans ATCC 10231, using agar well diffusion method on AWDT and Minimum Inhibitory Concentration (MIC). The results of the antibacterial activity are expressed by the diameters of the inhibition zones. Concerning the argan's leaves extract, the results differ from one strain to another, they are between 19mm and 26mm respectively for S. aureus ATCC 33862 and Salmonella typhimurium ATTC 14028. The activity of the argan's powder diameters are between 18 and 10 mm for S. aureus ATCC 33862 and C. albicans ATCC 10231 respectively. The highest recorded MIC values is recorded by Salmonella typhimurium ATTC 14028 with a value of 12.5 mg/μl for the extract and 100 mg/μl for the powder. The lowest MIC is recorded by S. aureus ATCC 33862 and C. albicans ATCC 10231 with a value of 6.25 mg/μl for the extract, concerning the powder, values of 25 mg/μl were recorded for the two strains. All the results indicate that the extract as well as the powder of the leaves of Argania spinosa have a very interesting and significant effect against the pathogens tested. The highest recorded MIC values are recorded by Salmonella typhimurium ATTC 14028 with a value of 12.5 mg/μl for the extract and 100 mg/μl for the powder. The lowest MIC is recorded by S. aureus ATCC 33862 and C. albicans ATCC 10231 with a value of 6.25 mg/μl for the extract, concerning the powder, values of 25 mg/μl were recorded for the two strains. All the results indicate that the extract as well as the powder of the leaves of Argania spinosa L. Skeels have a very interesting and significant effect against the pathogens tested.
Keywords: Argania spinosa L.; Skeels; Antimicrobial activity; pathogenic strains; MIC